As múltiplas funções da agricultura familiar: um estudo no assentamento Monte Alegre - Araraquara/SP - Gavioli, Felipe Rosafa (Universidade Federal de São Carlos, 2010)
From the emergency of the idea of sustainability, agriculture has acquired new connotations beyond the productive aspect, and associated with conservation of natural resources and rural territories, in recognition of their multifunctionality. Based on this concept, which values the socioenvironmental functions performed by rural families, the present work made an analysis on the rural settlement Monte Alegre, in the state of São Paulo, and identifies the functions beyond the production and their expression in this particular territory. The research starts form the hypothesis that family farming, by its polyvalence and by its sociocultural aspects, has the potential to conserve natural resources, ensuring food security of society, maintain cultures and ways of life in the countryside, among other aspects that are tributaries of the practice of agriculture. With a methodology based on qualitative and quantitative information, it was observed that the focused settlement has an agriculture that carries with it questions of identity, territorial cohesion, agrobiodiversity conservation and encouragement to other productive activities being the central element of the rebuild of a rural way of life in this environment.
The multiple functions of family agriculture: a case studying in the Monte Alegre rural settlement - Araraquara/SP
Keywords: Agroecologia; Agricultura familiar; Desenvolvimento rural; Assentamentos rurais; CIENCIAS AGRARIAS